POSITIVE LANGUAGE ATTITUDES AND MOTIVATION AFFECT STUDENTS’ PROFICIENCY AND PERFORMANCE IN LEARNING ENGLISH AS A SECOND LANGUAGE - Salainti, Engelina (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
Many factors affect someone's learning of English. It can be the learners themselves and their environment. Several students aim to achieve a high stage of proficiency in English, but various obstacles hinder their progress. Some positive and negative language attitudes affect students' achievement and performance in English. Negative language attitudes affect students' achievement and performance in English, such as feeling shy, lazy, or uninterested in practicing and using the language. In this journal the researcher would like to find and share how a Positive Language Attitude affects proficiency and performance in English. The researcher will use a qualitative approach to conduct a survey using questionnaires to collect the data and read through all the results of the questionnaires to draw some of the effects between positive language attitudes and motivation toward students' proficiency and performance in Learning English as a second language. There are 50 students from Pre-Elementary Class F at Universitas Klabat Manado which the researcher chose to be the participants. As a result, the students can increase their achievement and performance in English by having a positive language attitude and being highly motivated.